2019
DOI: 10.1186/s12891-019-2573-5
|View full text |Cite
|
Sign up to set email alerts
|

Is treated HIV infection associated with knee cartilage degeneration and structural changes? A longitudinal study using data from the osteoarthritis initiative

Abstract: Background Metabolic disorders presenting in HIV-infected patients on antiretroviral therapy (ART) may increase the risk of osteoarthritis. However, structural changes of the knee in HIV infected subjects are understudied. The aim of this study is to investigate knee cartilage degeneration and knee structural changes over 8 years in subjects with and without HIV infection determined based on the use of ART. Methods We studied 10 participants from the Osteoarthritis Init… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 45 publications
0
14
0
1
Order By: Relevance
“…Our study has several limitations. We graded size and highest signal of IPFP signal alterations as previously reported [17], but most previous studies focused only on size of signal alterations by using the MOAKS grading system [16], a subjective score differentiating mild to severe grades, and another study used a more detailed grading with 0 = normal; 1 = < 10% signal abnormality of the region; grade 2 = 10-20% of the region; and grade 3 > 20% of the region [41]. However, we demonstrated that both size and degree of signal intensity of IPFP abnormalities potentially contributed to a good surrogate marker for synovial inflammation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our study has several limitations. We graded size and highest signal of IPFP signal alterations as previously reported [17], but most previous studies focused only on size of signal alterations by using the MOAKS grading system [16], a subjective score differentiating mild to severe grades, and another study used a more detailed grading with 0 = normal; 1 = < 10% signal abnormality of the region; grade 2 = 10-20% of the region; and grade 3 > 20% of the region [41]. However, we demonstrated that both size and degree of signal intensity of IPFP abnormalities potentially contributed to a good surrogate marker for synovial inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, six sub-features were graded per knee as described in previous publications (Table 1) [15][16][17][18]. As it is not always possible to differentiate synovial thickening from intra-articular joint fluid on NCE-MRI, we used the term effusion-synovitis as previously described [16,18].…”
Section: Synovial Inflammatory Markersmentioning
confidence: 99%
See 1 more Smart Citation
“…The University of California San Francisco (UCSF)modified whole-organ MRI score (WORMS) system was used to semi-quantitatively assess OA-related knee morphological abnormalities [19][20][21]. Meniscal lesions were graded from 0 to 4 in each of 6 regions (anterior/body/ posterior regions of the medial and lateral menisci) using the following 4-point scale: 0 = normal, 1 = intrasubstance signal, 2 = nondisplaced tear, 3 = displaced or complex tear, and 4 = complete destruction/maceration.…”
Section: Worms Scoringmentioning
confidence: 99%
“…У ВИЧ-инфицированных пациентов, как правило, отмечается более тяжелое течение ОА с быстрым эрозированием суставных поверхностей. Было установлено, что пациенты с гонартрозом, получавшие АРВТ по поводу ВИЧ, имели более неоднородное состояние хрящевого матрикса, более тяжелый синовит и аномалии над-и поднадколенниковых жировых тел по сравнению с больными ОА без ВИЧ [15]. Сходные данные были получены A.L.…”
unclassified